APLIKASI IDENTIFIKASI KEMATANGAN PISANG DENGAN METODE THRESHOLDING DAN RGB RATIO - Mawaddah Harahap; Steven Steven; Justin Handoko Wijaya; Willyanto Willyanto; Yan Sentosa Nainggolan; Jon Rika Sitepu (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2019)
Banana is a kind of berry fruit which has ovaled shape and has yellow, green or brown color with smooth flesh and commonly sweet. Almost all banana has yellow skin while ripe, although some of them have orange, red, green, purple or even black. Color space consists of crominant and luminant component, whereas element that is often used for skin color is crominant element and use RGB and YCbCr, because this YCbCr color space achieve the best result for skin. Skin color detected could be used to determine maturity level of banana. The process of identification of banana maturity will begin by changing the inserted RGB image into a grayscale image. After that, the grayscale image obtained will be converted into a black and white image so that objects can be grouped in it. Then, the pixel color of the image in the detected area will be changed to the YCbCr color space. Based on the YCbCr value obtained, the level of maturity of the banana will be detected. RGB Ratio method could be used to detect banana maturity level accurately. Application achieved could be used to detect banana maturity level for input image. Based on the results of testing process, obtained information that the accuracy of the identification process of banana maturity is 90%.